Systematic Literature Review Of Leadership Change And Employee Rotation On Public Organizational Performance At The Directorate General Of Taxes - Muhammad Rafi Abdillah; Yudi Nur Supriadi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
This study analyzes the influence of leadership change and employee rotation on organizational performance in public organizations through a Systematic Literature Review (SLR). The study collected scientific articles indexed in Scopus and Google Scholar using Publish or Perish. The selected literature was analyzed using the PRISMA procedure and bibliometric analysis with VOSviewer to identify research trends, dominant topics, and relationships among variables. The findings indicate that leadership change and employee rotation affect organizational effectiveness, employee competence, work motivation, and organizational adaptability. Competency-based leadership change tends to strengthen strategic direction and organizational performance, while employee rotation contributes to competence development, work flexibility, and productivity. However, inappropriate leadership placement and rotation that do not match employee competence may reduce organizational effectiveness, especially in hierarchical public organizations with high performance pressure. The review identifies organizational culture, communication systems, competency management, and employee adaptability as important conditions that shape the effectiveness of both policies. In the context of the Directorate General of Taxes, the findings underline the importance of competency-based human resource management in supporting bureaucratic reform and sustainable performance improvement.